2021
DOI: 10.1002/asia.202100487
|View full text |Cite
|
Sign up to set email alerts
|

Diaminomethylenemalononitrile as a Chiral Single Hydrogen Bond Catalyst: Application to Enantioselective Conjugate Addition of α‐Branched Aldehydes

Abstract: An improved diaminomethylenemalononitrile organocatalyst, bearing a N,N‐disubstituted structure, promoted enantioselective conjugate addition reaction of α‐branched aldehydes with vinyl sulfone, affording adducts with excellent enantioselectivities (up to 96% ee). Mechanistic studies revealed that the diaminomethylenemalononitrile motif holds the vinyl sulfone substrate using a single hydrogen bond accompanied by multiple weak interactions, including electrostatic C−H⋅⋅⋅O interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…More recently, the Yanai and Miura group described the enantioselective Michael addition of α-aryl propanaldehydes to vinyliden bis(sulfones) promoted by their diaminomethylenmalononitrile/primary amine catalyst C48 ( Scheme 20 ) [ 77 ]. Using trifluoroacetic acid as an additive in dichloromethane as the solvent, excellent enantioselectivities of the respective α-quaternary aldehyde adducts were obtained under smooth conditions (RT, 24 h).…”
Section: Methods Based On Enamine Activationmentioning
confidence: 99%
“…More recently, the Yanai and Miura group described the enantioselective Michael addition of α-aryl propanaldehydes to vinyliden bis(sulfones) promoted by their diaminomethylenmalononitrile/primary amine catalyst C48 ( Scheme 20 ) [ 77 ]. Using trifluoroacetic acid as an additive in dichloromethane as the solvent, excellent enantioselectivities of the respective α-quaternary aldehyde adducts were obtained under smooth conditions (RT, 24 h).…”
Section: Methods Based On Enamine Activationmentioning
confidence: 99%
“…In our previous report, we demonstrated that the asymmetric conjugate additions of aldehydes to vinyl sulfone could be achieved using the bifunctional organocatalysts bearing chiral cyclohexane diamine and N ‐monoalkyl DMM motifs [6] . Recently, we reported that the N , N ‐dibenzyl DMM organocatalyst achieved higher stereoselectivity in the asymmetric conjugate additions of aldehydes to vinyl sulfone than the N ‐monobenzyl DMM catalyst [7] . Furthermore, the N , N ‐dibenzyl DMM organocatalysts enhance asymmetric Henry reactions between trifluoromethyl enones and nitromethane, giving the products of 1,2‐adducts with high enantioselectivities [8] .…”
Section: Methodsmentioning
confidence: 99%
“…[6] Recently, we reported that the N,N-dibenzyl DMM organocatalyst achieved higher stereoselectivity in the asymmetric conjugate additions of aldehydes to vinyl sulfone than the N-monobenzyl DMM catalyst. [7] Furthermore, the N,N-dibenzyl DMM organocatalysts enhance asymmetric Henry reactions between trifluoromethyl enones and nitromethane, giving the products of 1,2-adducts with high enantioselectivities. [8] To demonstrate the usefulness of the N,N-dibenzyl DMM organocatalysts, we applied them to other high-value asymmetric reactions.…”
mentioning
confidence: 99%
“… [24] In 2021, Miura conducted the DFT simulation to reveal the reaction mechanism. The diaminomethylmalononitrile organic catalyst was not only used as hydrogen bond donor, but also the push pull effect in its backbone could effectively enhance the multiple noncovalent interactions, including the C−H−O interaction, to stabilize the transition state [25] …”
Section: Synthesis Of Chiral Sulfones By Asymmetric Michael Additionmentioning
confidence: 99%